1996
DOI: 10.1002/(sici)1097-0193(1996)4:2<103::aid-hbm2>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation causes increased blood flow to the anterior cingulate cortex

Abstract: Increased cerebral blood flow in the anterior cingulate cortex (ACC) has been noted in a range of cognitively demanding tasks studied with PET. A PET study of 10 normal males was carried out using the bolus H2150 intravenous injection technique to examine the effects of anticipation on blood flow to the ACC. In a series of conditions, subjects 1) passively viewed flashing plus signs, 2) noted the occurrence of abstract patterns, 3) named animal pictures, 4) or carried out a semantic judgement on animal picture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 0 publications
4
56
0
Order By: Relevance
“…Monkey single-unit data (24) and human fMRI data (19) clearly indicate that dACC responds well in advance of stimuli-a fact other theories cannot adequately incorporate. Also, the fact that monkey single-unit studies (24)(25)(26)(27) repeatedly show responses by different cells at different times (prestimulus, preresponse, peri-response, postresponse) presents a puzzle for alternative, unimodal theories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monkey single-unit data (24) and human fMRI data (19) clearly indicate that dACC responds well in advance of stimuli-a fact other theories cannot adequately incorporate. Also, the fact that monkey single-unit studies (24)(25)(26)(27) repeatedly show responses by different cells at different times (prestimulus, preresponse, peri-response, postresponse) presents a puzzle for alternative, unimodal theories.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although competition monitoring and task difficulty cannot explain all of the data, they are factors that would be predicted to yield increased dACC activity, because diverse dACC cell types would be recruited by cognitively difficult tasks such as those requiring the resolution of competition. Thus, in addition to readily explaining activity during many reward-based decision making and other complex response selection tasks (such as the Stroop, Stroop-like, Eriksen Flanker, divided attention, go-nogo, and verb generation tasks) (1), the heterogeneity concept has the unique capacity to explain anticipatory (prestimulus) activity (1,19), error feedback activity (16), and reward-and-punishment activity (22)-observations that existing theories have difficulty accounting for (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no reason that tonechange condition needs more attention than vowel-change condition. An alternative explanation is that the activation of anterior cingulate gyrus may be attributed to the participants' preparation, planning, and anticipation of the cognitive task rather than taskrelated processing itself (Murtha et al, 1996). Further evidence is needed to support this point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Like the ventral striatum, the ACC is involved in reward processing and it also seems to be sensitive to the magnitude of a received reward (Bush et al, 2002;Peoples, 2002;Shidara and Richmond, 2002;Kirsch et al, 2003). It has also been shown to have a role in anticipation (Murtha et al, 1996). In conditioning studies, the ACC was found to discriminate between a reinforced CS (CS + ) and a nonreinforced CS (CS-) (Martin-Soelch et al, 2007).…”
Section: Neural Impact Of Begin-and End-stimuli In Nondeprived Smokersmentioning
confidence: 99%